(untitled) (Zoological Records and Reviews, 2022)
Urban freshwater bodies – including city lakes, retention ponds, ornamental tanks, storm-water basins, and urban canal systems – represent a globally expanding habitat type whose biodiversity is poorly documented relative to their potential ecological significance. While urban water bodies are frequently dismissed as degraded and ecologically depauperate, emerging evidence from European cities suggests they can support unexpectedly diverse macroinvertebrate and macrophyte assemblages and serve as refugia for certain freshwater taxa in heavily urbanised landscapes. This study presents a comprehensive multi-taxon biodiversity survey of freshwater organisms across 48 urban water bodies in three Asian megacities – Hyderabad, India; Colombo, Sri Lanka; and Dhaka, Bangladesh – using standardised protocols for phytoplankton, zooplankton, macroinvertebrates, macrophytes, and fish. A total of 684 freshwater taxa are documented across all groups and cities, comprising 184 phytoplankton taxa, 128 zooplankton taxa, 212 macroinvertebrate species, 84 macrophyte species, and 76 fish species. Urban water body age, connectivity to natural water bodies, and surrounding green cover are the strongest predictors of total biodiversity. Hyderabad’s historic tank system – a network of over 3,000 interconnected water bodies – supports the highest per-water-body biodiversity of the three cities. Invasive species – particularly Eichhornia crassipes, Gambusia affinis, and Pomacea canaliculata – are documented in 68.8% of surveyed water bodies and are identified as a major threat to native biodiversity. Management recommendations for enhancing urban freshwater biodiversity are provided.